PEDAGOGICAL TECHNOLOGIES OF INTEGRATION OF FOREIGN STUDENTS INTO EDUCATIONAL SPACE OF HIGHER EDUCATION INSTITUTION (ON THE EXAMPLE OF STUDENTS FROM THE PEOPLE'S REPUBLIC OF CHINA) - Tat'yana L. Guruleva (Высшее образование в России)
The article addresses pedagogical technologies of integration of foreign students into the educational space ofRussian higher education institution. According to the author, the called pedagogical technologies include technologies of training, and also technology of sociocultural integration of foreign students into the Russian society and culture. A special attention is paid to the training technologies aimed at integration of foreign students into educational process ofRussian higher education institution. It is defined that the technologies of training of foreign students in international groups represent a combination of specially adapted interactive methods of training and multilingual information technologies. The conditions of use of interactive methods of training in groups with an international structure of students are revealed. On an example of the international groups including Chinese students the author explores specifics of application of the pedagogical training technologies promoting integration of foreign students into educational process.